2007
DOI: 10.1377/hlthaff.26.3.726
|View full text |Cite
|
Sign up to set email alerts
|

Informed Patient Choice: Patient-Centered Valuing Of Surgical Risks And Benefits

Abstract: ABSTRACT:The risks and benefits of any health care intervention are valued differently by stakeholders. One of the ethical imperatives of patient-centered care is the balanced, evidence-based presentation of risks and benefits by providers to patients. Using the example of musculoskeletal surgery with devices, we advocate the use of shared decision-making tools and processes known to improve knowledge, adjust unrealistic expectations, and elicit values about benefits desired and the degree of acceptable risks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 12 publications
1
71
0
Order By: Relevance
“…High-quality shared-decision-making discussions involve eliciting patients' preferences, which is not a common diagnostic skill among most currently practicing providers. 6 Further research is needed to confirm whether the decision aids influence patient-provider interactions in this setting (including satisfaction with care), or whether decision aids influence patients' preferences independent of the patient-provider encounter.…”
Section: Study Data and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-quality shared-decision-making discussions involve eliciting patients' preferences, which is not a common diagnostic skill among most currently practicing providers. 6 Further research is needed to confirm whether the decision aids influence patient-provider interactions in this setting (including satisfaction with care), or whether decision aids influence patients' preferences independent of the patient-provider encounter.…”
Section: Study Data and Methodsmentioning
confidence: 99%
“…6 Shared decision-making processes often incorporate decision aids, which are balanced sources of information about treatment options for a particular health condition. 6,7 A recent review of eighty-six randomized trials of decision aids found that these aids consistently increase patients' knowledge; improve treatment expectations; increase active participation in decision making; reduce decisional conflict or uncertainty about the appropriate course of action; decrease the proportion of people remaining undecided about treatment; and help patients reach decisions that are more aligned with their stated values. 8 Seven randomized trials have addressed decision making about elective surgical treatments, although no prior trials included hip and knee replacement procedures.…”
Section: Introducing Decision Aids At Group Health Was Linked To Sharmentioning
confidence: 99%
“…10 The term SDM is often used inconsistently. 11,12 The following elements characterize our understanding of SDM [13][14][15][16][17][18] : SDM may (and should) be employed in life-threatening disease, where biomedical factors far outweigh placebo effects in determining the outcome. Nevertheless, physicians frequently encounter treatment decisions involving chronic and self-limited illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…According to the law, the patient must be informed about the diagnosis and its uncertainties, the purpose, benefits and risks of the recommended treatment, other treatment choices and their benefits and risks, and potential complications (1,2,(4)(5)(6)(7)(11)(12)(13)(14). With sufficient information, the patient can decide whether or not to go ahead with the surgery, knowing the risks of refusing or accepting the treatment (1,5,13). "Sufficient information" is a critical term here; it is the doctor's responsibility to find out how much a patient wants to and should know about the condition and its treatment options (1).…”
Section: Discussionmentioning
confidence: 99%